Improved Skin Wound Healing Activity of Insulin Cream as Evidenced from the Morphological Evaluation in Guinea Pigs - Mohamed, NAH; Mokhtar, RH; Al-Ani, IM; Ayob, A; Misran, M (Univ Indonesia, 2024)
Indexed by WOS